Early Diagnosis and Prognosis of Hereditary Breast Cancer - Baxramova Gulzirabonu; Djalolova Feruza (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Hereditary breast cancer represents a highly aggressive subset of oncological pathologies, primarily driven by pathogenic germline mutations in highly penetrant susceptibility genes such as BRCA1, BRCA2, TP53, and PALB2. This comprehensive review elucidates the critical imperatives of early diagnosis and prognostic evaluation specifically tailored to the hereditary breast cancer phenotype. By synthesizing contemporary clinical guidelines, advanced molecular screening protocols, and longitudinal prognostic data, this study highlights the paradigm shift from generalized population screening to individualized, genetically-guided surveillance. The integration of high-resolution magnetic.